Structural and functional brain connectomes in patients with systemic lupus erythematosus. (8th August 2019) - Preziosa, P.; Rocca, M. A.; Ramirez, G. A.; Bozzolo, E. P.; Canti, V.; Pagani, E.; Valsasina, P.; Moiola, L.; Rovere‐Querini, P.; Manfredi, A. A.; Filippi, M.
Abstract : Background and purpose: Systemic lupus erythematosus (SLE) is an immune‐mediated disease that may affect the nervous system. We explored the topographical organization of structural and functional brain connectivity in patients with SLE and its correlation with neuropsychiatric (NP) involvement and autoantibody profiles. Methods: Graph theoretical analysis was applied to diffusion tensor magnetic resonance imaging (MRI) and resting‐state functional MRI data from 32 patients with SLE and 32 age‐ and sex‐matched healthy controls. Structural and functional connectivity matrices between 116 cortical/subcortical brain regions were estimated using a bivariate correlation analysis, and global and nodal network metrics were calculated. Results: Structural, but not functional, global network properties (strength, transitivity, global efficiency and path length) were abnormal in patients with SLE versus controls ( P  <   0.0001), especially in patients with anti‐double‐stranded DNA (ADNA) autoantibodies ( P  =   0.03). No difference was found according to NP involvement or anti‐phospholipid autoantibody status. Patients with SLE and controls shared identical structural hubs and the majority of functional hubs. In patients with SLE, all structural hubs showed reduced strength and clustering coefficient compared with controls ( P from 0.001 to <0.0001), especially in patients with ADNA autoantibodies. Only a few differences in functional hub properties were found between patients with SLE and controls. Structural and functional hub measures did not differ according to NP involvement or anti‐phospholipid autoantibody status. Significant correlations were found between clinical, MRI and network measures ( r from −0.56 to 0.60, P from 0.0003 to 0.05). Conclusions: Abnormalities of global and nodal structural connectivity occur in patients with SLE, especially with ADNA autoantibodies, with a diffuse disruption of structural integrity. Functional network integrity may contribute to preserve clinical functions.